Leaf macro- and micromorphological traits and phenotypic diversity of Quercus petraea subspecies in Eastern Romania - Ioana M. GAFENCO (PLEȘCA); Ecaterina N. APOSTOL; Bogdan I. PLEȘCA; Elena CIOCÎRLAN; Dan M. GUREAN; Neculae ȘOFLETEA (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Sessile oak (Quercus petraea) is a polytypic species comprising three subspecies (Q. petraea subsp. petraea – Qpe, Q. petraea subsp. dalechampii – Qda, and Q. petraea subsp. polycarpa – Qpo) with distinct ecological requirements, posing significant challenges in morphological differentiation. The integration of macro- and micro-morphological analyses plays a crucial role in clarifying the taxonomic uncertainties. This study aimed to characterize phenotypic diversity and identify key leaf descriptors for distinguishing sessile oak subspecies across three peripheral populations, one reference population, and one sessile oak comparative trail from Eastern Romania. A comprehensive analysis was conducted on 227 sampled trees, utilizing multivariate statistical analysis - encompassing 18 macromorphological and 9 micromorphological leaf descriptors. The results revealed distinct traits of Qda and Qpo, including shorter leaves with maximal width in the lower half of the lamina, fewer lobes, ovate shapes, a subcordate basal shape, and a higher intercalary vein frequency compared to Qpe. Furthermore, Qpo could be differentiated from both Qpe and Qda by its shorter lamina lengths, fewer lobes, greater lobe width ratios, and stellate trichomes with shorter rays. The length of rays of stellate trichomes has emerged as a significant micromorphological descriptor. Qda predominated in peripheral populations, likely due to natural selection in drought-affected local ecosystems. This highlights the importance of prioritizing this taxon in breeding programs and conserving it in situ, given its remarkable leaf plasticity and adaptability. Additionally, principal component indicated a fairly high level of morphological similarity among the three subspecies. These findings emphasize the critical importance of comprehensive morphological analyses for precise species classification and deeper understanding of sessile oak taxonomy.